A participação cooperativista dos avicultores na região oeste paranaense - Belusso, Diane [UNESP] (My University, 2012)
This study deals with the cooperative participation of the aviculturists as associated with integrating companies. From the survey, it was evident that the cooperative participation involves a higher level organization of these farmers. However, they comprise a minority in the general framework of cooperatives, because poultry keeping is just one economic activity among diverse others. Cooperative enterprises intensify the farmers' claims to government, mainly for rural credit policies, interfering in the efficient use of resources and in the productive options.
The cooperativist participation of the aviculturists in Western Paraná
Keywords: Cooperative enterprises; Integrated producers; Poultry industry